2012
DOI: 10.1089/apc.2011.0303
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing HIV in Men Who Have Sex with Men: An Emergency Department's Experience

Abstract: In the United States, men who have sex with men (MSM) constitute the risk group in which the prevalence of new HIV infection is increasing. The percentage of undiagnosed HIV infection and HIV risk behaviors in MSM and non-MSM participating in an emergency department-based rapid HIV screening program were compared. Medical records of all male patients participating in the program from May 2008 to October 2010 were reviewed. MSM were identified as male or male-to-female patients reporting oral and/or anal sex wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Our findings are consistent with those from studies in other countries where HIV stigma, social discrimination, and perceived low HIV risk create barriers to HIV testing uptake; [35][36][37] and recent high risk behaviors (e.g., condomless anal sex), free and rapid testing techniques encourage testing. 36,38,39 Specific to work conducted to date with MSM in China, 3,29,30,[40][41][42] our findings similarly identify stigma and a poor understanding of HIV and transmission dynamics as a major factors in both testing as well as linkage and retention in HIV-care.…”
Section: Discussionsupporting
confidence: 58%
“…Our findings are consistent with those from studies in other countries where HIV stigma, social discrimination, and perceived low HIV risk create barriers to HIV testing uptake; [35][36][37] and recent high risk behaviors (e.g., condomless anal sex), free and rapid testing techniques encourage testing. 36,38,39 Specific to work conducted to date with MSM in China, 3,29,30,[40][41][42] our findings similarly identify stigma and a poor understanding of HIV and transmission dynamics as a major factors in both testing as well as linkage and retention in HIV-care.…”
Section: Discussionsupporting
confidence: 58%
“…In addition vulnerable patients (i.e., persons with substance abuse, homelessness, mental health problems, and victims of violent crime) are 1.4 to 2 times more likely to seek care in the ED compared to primary care settings . Numerous studies have demonstrated that the ED population has a higher prevalence of human immunodeficiency virus (HIV) infection compared to antenatal clinics and other outpatient settings and thus may be an unique high‐impact venue for HIV testing and treatment interventions . It can be hypothesized that globally further research is necessary to define the role of emergency care services in capturing vulnerable populations that are otherwise missed by healthcare system for public health interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Sex and racial disparities in HIV incidence at the national level impact males more than females. African American males are most impacted by the HIV epidemic 27 . This national HIV burden extends to African Americans locally, because this racial group is over‐represented in those tested for HIV in the ED and even more so among those testing positive for HIV.…”
Section: Discussionmentioning
confidence: 99%